Improving Attendance Management in Educational Institutions: A Model View Controller Approach - Singh, Rudra Pratap; Arora, Madhav; Singh, Gurwinder (International Journal of Computer Sciences and Engineering, 2026)
T Efficient attendance management plays a crucial role in the success of educational institutions. This paper proposes a novel approach to enhance attendance management through the utilization of the Model-View-Controller (MVC) architecture. Traditional manual methods for attendance calculation are prone to errors and time-consuming. To address these challenges, an effective web application is designed to electronically monitor student activity in the classroom and store attendance records in a database. The application leverages the power of the Laravel Framework and incorporates JavaScript for improved usability. By implementing the MVC architecture, the system enables easy manipulation of attendance data through a user-friendly graphical user interface (GUI). Moreover, the system takes into account the distinction between theoretical and practical teaching hours, facilitating accurate calculation of student absences. The successful implementation and testing of the system demonstrate its readiness to manage student attendance in any department of a university. This paper provides valuable insights into leveraging MVC architecture for attendance management and offers a practical solution to enhance efficiency and accuracy in educational institutions